1998
DOI: 10.1038/sj.bmt.1701224
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive immunotherapy for relapse of chronic myeloid leukemia after allogeneic bone marrow transplant: equal efficacy of lymphocytes from sibling and matched unrelated donors

Abstract: Summary:Lymphocyte transfusion from the marrow donor (DLT) is well established as an effective therapy for relapse of CML post allogeneic BMT. Reports thus far have been mostly limited to patients who received DLT from a matched sibling donor. We compared the efficacy and toxicity of DLT in 30 patients who were treated with cells from their HLA-identical sibling (n = 18) or from their phenotypically HLA-matched unrelated marrow donor (n = 12). The overall probability of obtaining a cytogenetic remission was 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 13 publications
1
29
1
Order By: Relevance
“…5,14,21,22 Remission rates of DLI for early-phase relapse were reported to be 82-100%, 5,[13][14][15][16] which are higher than the 65% of the present study. However, several points should be considered when comparing our results with previous results.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…5,14,21,22 Remission rates of DLI for early-phase relapse were reported to be 82-100%, 5,[13][14][15][16] which are higher than the 65% of the present study. However, several points should be considered when comparing our results with previous results.…”
Section: Discussioncontrasting
confidence: 54%
“…Some data regarding immunotherapy for early-phase relapse exist, but the relapse time after transplant is variable as is the dose of T cells infused. 5,[13][14][15][16] Accordingly, treatment results and the toxicities of early-period immunotherapy for early-phase relapse are not well known.…”
mentioning
confidence: 99%
“…We have read with interest the article of van Rhee et al 1 dealing with donor lymphocyte transfusion (DLT) for treatment of CML relapse in patients after BMT. Among other aspects the authors touch on the problem of durability of remissions after DLT treatment.…”
Section: Late Molecular Relapse In Two CML Patients In Molecular Remimentioning
confidence: 99%
“…Most commonly, the DLI product is obtained by leuka- Table 3 Response and toxicity after unrelated donor leukocyte infusion for treatment of relapsed acute leukemia 47 Indication N CR (%) DFS (%) aGVHD (%) grade II-IV cGVHD (%) extensive Aplasia (%) 51 Since the precise effector of GVL is unknown, unfractionated blood mononuclear cell infusions have the benefit of providing a spectrum of alloreactive and other immune accessory cells. This may increase the likelihood of a response although it is reproducibly associated with significant toxicity from GVHD.…”
Section: Cellular Componentsmentioning
confidence: 99%
“…The two large registry studies suggested that UDLI and related DLI result in similar outcomes but included small number of patients, 9,10 and the other study using DLI for relapsed CML found no significant difference in outcomes using matched sibling or unrelated donor DLI. 47 There has been a retrospective analysis of recipients of UDLI identified through the National Marrow Donor Program database that included 23 patients with relapsed AML and 7 patients with relapsed ALL. 48 The median UDLI cell dose administered was 1.0 Â 10 8 mononuclear cells (MNC)/kg and 21% of patients were HLA-mismatched.…”
Section: Unrelated Donor Lymphocyte Infusionsmentioning
confidence: 99%